Writing Permitted in Designated Areas Only - Brodkey, Linda (Book collections on Project MUSE., 1996)
Ranging from personal essay to hard-hitting polemic and touching on many of the major issues in the teaching of writing today, this volume explores alternatives to the standard methods for teaching composition.